Perancangan Board Game Edukasi Financial Management Usia 11-12 Tahun - Kezia Mulianto; T. Arie Setiawan Prasida; Jasson Prestiliano (Pusat Riset dan Inovasi Nasional, 2025)
The low level of financial literacy in Indonesia, which only reached 49.68% according to the Financial Services Authority (OJK) in 2022, highlights the urgency of financial education from an early age. Children aged 11–12 are at an ideal developmental stage to understand basic financial concepts such as income, expenses, saving, and delayed gratification. This study aims to introduce financial literacy through an interactive learning medium in the form of a board game. Board games are chosen because they enhance children's engagement in learning while playing and serve as an alternative to excessive gadget use. Through gameplay, children practice financial decision-making by simulating buying and selling activities, managing expenses, and choosing to save. This approach also supports the development of children's self-efficacy, which refers to their belief in their ability to manage financial tasks. By applying this method, children are expected not only to understand the value of money but also to implement basic financial management skills in daily life. Educational board games offer an effective tool for instilling healthy financial habits from an early age.